Procedural aspects of a settlement reached before the court in the course of proceedings - Ilków, Diana (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2013)
The study aims on the procedural aspect of a settlement reached before the court in the course of proceedings. Procedural rules indicate when and in what circumstances the court has to persuade the parties to reconcile and what should be the nature of that action. In addition, the procedural law complements the range of possible reciprocal concessions made by the parties. It also sets out further requirements that have to be followed by the body of a settlement reached before the court, especially by indicating the extent of judicial control. The rules of the civil procedure also determine the effect that a settlement reached before the court has on the course of further proceedings. Thus,the aim of the above is that the rules are focused on the implementation of the postulate expressed in Article 10 of the Civil Procedure Code.